Tourism in Moscow after the ‘Perestroika’ transformations - Aleksandrova, Anna Y. (Turyzm/Tourism, 2012)
Moscow seems indeed to be a centre of world tourism. On the one hand, its tourism attractiveness for Russians and foreigners, as well as the wide opportunities it offers to its own inhabitants, stimulates trips for tourism and recreational purposes. On the other hand, it is determined by a number of historical, geographical, demographic, geopolitical, economic and socio-cultural factors.